Cassirer, la critique de la confusion dans la culture comme transvaluation mythico-magique - Leonore Bazinek; Marie-Louise Martinez (Université de Provence, 2017)
For Ernst Cassirer, the confusion marking a cultural crisis is always linked to the resurgence of mythical thought. In order to understand the current confusion, our study proposes to refer at the philosophical reflections of Cassirer and their anthropological inspiration, in particular the notions of indifferentiation and "scapegoat" as categories of the mythico-magic. A privileged place is granted to this author whose philosophy of symbolic forms offers invaluable analytical and critical resources hitherto little recognized.